Kejadian Misfile Sebagai Pemicu Penghambat Data Rekam Medis - andhy sulistyo andi (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Background: This research was motivated by the occurrence of misfiiles from 1332 medical record files located on the storage rack from medical record file rack numbers 9002 to 0504 found 23 medical record files that were not in place or misfiiles at Prambanan Health Center. This causes the patient service process to be hampered, the patient's medical record data cannot be sustainable. Objective: This study aims to determine the factors that cause misfiiles of medical record files in the storage room of Prambanan Health Center. Methods: This study uses a descriptive method with a qualitative approach. The data collection of this research was carried out by the researcher by means of interviews and observations. The population of this study consisted of two officers in the medical record file storage section with triangulation of sources. Results: Misfiile events from the number of misfiile calculations 9 medical record files from 55 medical record files sought are known by the number of misfiile percentages as much as 16.36% and seen from the implementation of the file retrieval and storage flow has an impact on service time and the unsustainability of the patient's medical record data. caused by several factors, namely human resources, systems, medical record files are still in the polyclinic, not optimal use of tracers and infrastructure. Conclusion: Management of medical record files at Prambanan Health Center is centralized and a family folder storage system with a Straight Numerical Filing numbering system. Factors causing misfiile medical record files include human resources, systems and infrastructure.